Effects of cumulus clouds on microclimate and shoot-level photosynthetic gas exchange in Picea engelmannii and Abies lasiocarpa at treeline, Medicine Bow Mountains, Wyoming, USA (2020)
Here we describe the dynamic effects of cumulus clouds on microclimate and shoot-level photosynthetic gas exchange in saplings of two treeline conifer species—Picea engelmannii and Abies lasiocarpa. Measurements were made during both clear-sky and partly cloudy conditions (?10–70% cumulus cloud cover) throughout the 2012 growing season within an alpine-treeline ecotone. Cumulus clouds generated dynamic fluctuations in photosynthetically active radiation (PAR), higher maximum PAR (>2500 ?mol m?2 s?1), 2–4 fold increases in diffuse PAR, reduced daily mean and cumulative PAR, lower needle temperatures, and reduced leaf-to-air vapor pressure differences relative to clear-sky conditions. Onset of cloud-shade corresponded with declines in photosynthesis, needle temperatures, and evapotranspiration, which were proportional to cloud duration and opacity. Despite increased diffuse light and greater sunlight intensity during cloud-gaps, photosynthesis was never higher on partly cloudy days compared to clear days in either species, during cloud-gaps or cloud-shade. However, reduced transpiration paired with photosynthesis comparable with clear-sky levels during cloud-gaps resulted in greater instantaneous water use efficiency relative to clear-sky measurements. There was no apparent photoinhibition of photosynthesis reflected in gas exchange measurements in response to abrupt and dramatic changes in PAR levels caused by cumulus clouds. We conclude that cumulus clouds reduce instantaneous and daily carbon gain, although lower needle temperatures and associated reductions in transpirational water loss may alleviate daily and seasonal water stress, thereby enhancing carbon gain over the growing season